Impact of the anterior-posterior corneal radius ratio on intraocular lens power calculation errors - Hasegawa A (Dove Medical Press, 2018)
Asato Hasegawa,1 Takashi Kojima,2 Mana Yamamoto,1 Yukihito Kato,3 Akeno Tamaoki,1,4 Kazuo Ichikawa3 1Department of Ophthalmology, Japan Community Healthcare Organization Chukyo Hospital, Nagoya, Japan; 2Department of Ophthalmology, Keio University School of Medicine, Tokyo, Japan; 3Department of Ophthalmology, Chukyo Eye Clinic, Nagoya, Japan; 4Department of Mathematics and System Development, Shinshu University Interdisciplinary Graduate School of Science and Technology, Nagano, Japan Purpose: To evaluate the distribution of the anterior–posterior corneal radius ratio (AP ratio; anterior corneal radius/posterior corneal radius) in patients before cataract surgery, and investigate which parameters can affect this ratio. We also investigated the impact of the AP ratio on the intraocular lens (IOL) power calculation error in cataract surgery. Method: A total of 501 eyes of 501 consecutive patients who had no history of corneal diseases and had undergone cataract surgery were enrolled in this study. The patients’ AP ratio was measured before surgery using anterior segment optical coherence tomography; using these data, we evaluated the correlation between the AP ratio and various parameters that can affect the corneal radius. For subgroup analyses, we investigated the correlation between the AP ratio and IOL power calculation error in 181 eyes of 181 patients. Stepwise multiple regression analysis was performed with the IOL power calculation errors of the SRK/T, Haigis, Holladay 1, and Hoffer Q formulas as the dependent variables and various parameters that can affect the postoperative IOL power calculation error as the independent variables. Results: The mean AP ratio was 1.19±0.02, and it weakly correlated with corneal thickness, horizontal corneal diameter, and posterior corneal radius. The correlations between the AP ratio and IOL power calculation errors in the 4 calculation formulas were not statistically significant. Stepwise multiple regression analysis could not detect any significant parameters affecting this ratio. Conclusion: The AP ratio has no major influence on IOL power calculation error in patients with any history of corneal disease. Keywords: cataract surgery, anterior-posterior corneal radius ratio, intraocular lens power calculation